Persepsi Generasi Z terhadap Pembajakan Film Indonesia melalui TikTok dan Telegram - Fahrizzal, Farrel; Kusuma, Ade (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Generation Z is an active generation that uses online media. TikTok and Telegram are two forms of online media that are often used illegally to display scene clips or full durations of Indonesian films. Cases of film piracy are increasingly easy to find on online media. This study aims to explore Generation Z's perceptions of Indonesian film piracy on TikTok and Telegram online media. The research method used is descriptive qualitative with data collection techniques through in-depth interviews, documentation and literature studies. The study results show that Generation Z has various perceptions of film piracy, ranging from positive to negative. Film piracy can be in the form of displaying scene clips with limited durations on TikTok. Watching full-length films on Telegram is also part of the illegal distribution of films. Film piracy has the potential to harm filmmakers and does not respect copyright. However, filmmakers can still use TikTok for promotional media and attract the audience through scene clips displayed for a limited duration. The existence of video on demand can be an alternative for easy access to Indonesian films, which still need to be shown in theatres. In addition, the findings of this study explain the importance of further education on the negative impacts of piracy, increasing accessibility of legal content, and reducing dependence on pirated content through the availability of official platforms in the digital era.